2012
DOI: 10.1371/journal.pone.0035813
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Nse3/MAGE-Binding Domain of the Nse4/EID Family Proteins

Abstract: BackgroundThe Nse1, Nse3 and Nse4 proteins form a tight sub-complex of the large SMC5-6 protein complex. hNSE3/MAGEG1, the mammalian ortholog of Nse3, is the founding member of the MAGE (melanoma-associated antigen) protein family and the Nse4 kleisin subunit is related to the EID (E1A-like inhibitor of differentiation) family of proteins. We have recently shown that human MAGE proteins can interact with NSE4/EID proteins through their characteristic conserved hydrophobic pocket.Methodology/Principal FindingsU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 32 publications
5
36
0
Order By: Relevance
“…EID3, which was confirmed as a potential methylation marker, acts as a repressor of nuclear receptor-dependent transcription possibly by interfering with CREBBP-dependent coactivation. 34,35 This gene may function as a co-inhibitor of other CREBBP/EP300-dependent transcription factors. Its methylation/silencing likely unleashes the expression of several genes that promote cell proliferation and division.…”
Section: Discussionmentioning
confidence: 99%
“…EID3, which was confirmed as a potential methylation marker, acts as a repressor of nuclear receptor-dependent transcription possibly by interfering with CREBBP-dependent coactivation. 34,35 This gene may function as a co-inhibitor of other CREBBP/EP300-dependent transcription factors. Its methylation/silencing likely unleashes the expression of several genes that promote cell proliferation and division.…”
Section: Discussionmentioning
confidence: 99%
“…Despite earlier reports (5, 18), we have thus far not confirmed a physiological role for MDM2 in EID1 ubiquitylation, although MDM2 might polyubiquitylate EID1 under conditions not tested here. EID1 has several paralogs including EID2, EID2B, and EID3 (25)(26)(27)(28)(29)(30)(31)(32). The EID1 degron identified here is well conserved among the EID family members, and EID2 coimmunoprecipitates with FBXO21 in cells treated with MG132.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, it has been suggested that the EID and melanomaassociated antigen (MAGE) proteins are mammalian counterparts of yeast Nse4 and Nse3, respectively, which form an SMC complex involved in chromatin maintenance and DNA repair (30,32). Conceivably this function provides a teleological explanation for the induction of EID proteins during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In the SMC5/6 complex, MAGE-G1-NSE1 and NSMCE4 form a molecular bridge between SMC5 and SMC6 and are essential for complex formation [136, 137]. Interestingly, the two identified variants of MAGE-G1 result in p.Leu264Phe (L264F) and p.Pro209Leu (P209L), and were both shown to disrupt interactions with NSMCE4 and destabilize the SMC5/6 complex [135].…”
Section: Mages In Diseasementioning
confidence: 99%